1997
DOI: 10.1021/ef9601677
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation and Image Analysis for Evaluation of Swelling and Fluidity of Single Coal Particles Heated with CO2 Laser

Abstract: Swelling characteristics of three kinds of single coal particles heated with a well-characterized CO2 laser were directly observed and quantitatively evaluated by combined application of a high-speed video camera with an image analysis system. The results are as follows:  (1) The interval time between swelling and shrinking of bubbles of coking coal particles (Blue Creek, Goonyella) could be used to express the ease of reforming bubbles after bursting and the growth of the bubbles before bursting. The distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Interestingly, the particle size marginally affected the char swelling ratio as it increased from 1.58 for the char from −425 + 212 µm fraction to 1.65 for the char from −150 + 106 µm fraction. Earlier studies under pyrolysis observed that swelling (or porosity) decreased with an increase in coal particle size [17,44,45]. It is important to recognize that chars from the coarser size fractions are in early stages of conversion (<50%), while the chars from the fine-sized fractions (i.e., −106 + 75 and −150 + 106 µm) are in middle stages of conversion (50%-70%).…”
Section: Effect Of Feed Particle Sizementioning
confidence: 97%
“…Interestingly, the particle size marginally affected the char swelling ratio as it increased from 1.58 for the char from −425 + 212 µm fraction to 1.65 for the char from −150 + 106 µm fraction. Earlier studies under pyrolysis observed that swelling (or porosity) decreased with an increase in coal particle size [17,44,45]. It is important to recognize that chars from the coarser size fractions are in early stages of conversion (<50%), while the chars from the fine-sized fractions (i.e., −106 + 75 and −150 + 106 µm) are in middle stages of conversion (50%-70%).…”
Section: Effect Of Feed Particle Sizementioning
confidence: 97%
“…The thermoplastic behavior of coal particles during carbonization has thus been studied extensively with several types of analysis techniques and different kinds of coals. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Some researchers exhibit that coal thermoplasticity depends strongly on the amounts of chloroform solubles naturally-present in coal, 1,4,6) low-molecular-weight compounds (metaplasts) 2,3) and/or transferable hydrogen 7,10) formed upon carbonization. It has also been reported that the sulfur and nitrogen present in coal, denoted as coal-S and coal-N, respectively, affect coal fluidity, [17][18][19][20] and that the addition of denzo-[c]-acridine (C17H11N) to a coal blend, even at a small amount of 3 mass%, enhances the tensile strength of the coke after carbonization by a factor of about 1.2.…”
Section: Introductionmentioning
confidence: 99%
“…The growth, coalescence, and rupture of the bubbles lead to the swelling and shrinking of the coal particle during pyrolysis. A dynamic variation of the particle size because of multiple ruptures during coal pyrolysis has been observed, 9,10 and, overall, the change of particle size is an increasing then decreasing trend. Studies at low heating rates in thermogravimetric analysis (TGA) devices and wire mesh reactors indicate that the final swelling ratio of coal particle increases as the heating rate increases; 11 however, studies with drop-tube furnaces and flat-flame burners show that the swelling ratios decrease at rapid heating rates.…”
Section: Introductionmentioning
confidence: 94%